Analysis on Investigative Data Mining in the Counter-Terrorism, Technology and Transparency: Uncovering Valuable Data through Investigative Data Mining (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Data mining and data investigation is distinguishing, assembling, and handling the data that was broke down. To do this requires first recognizing what the investigation was expected to find and the kind of data that will be valuable. This isn't generally a straightforward errand. For data mining, analysts have created methods for dynamic realizing that can discover data that would be valuable to gather. The data mining process itself was regularly help with distinguishing sorts of data that are not valuable. One regular fantasy about data mining and computerized data investigation was that they expect data to dwell in one expansive database.